Pharmacologic inhibition of MLK3 kinase activity blocks the in vitro migratory capacity of breast cancer cells but has no effect on breast cancer brain metastasis in a mouse xenograft model. - Kun Hyoe Rhoo (PLoS ONE, 2014)
Brain metastasis of breast cancer is an important clinical problem, with few therapeutic options and a poor prognosis. Recent data have implicated mixed lineage kinase 3 (MLK3) in controlling the in vitro migratory capacity of breast cancer cells, as well as the metastasis of MDA-MB-231 breast cancer cells from the mammary fat pad to distant lymph nodes in a mouse xenograft model. We therefore set out to test whether MLK3 plays a role in brain metastasis of breast cancer cells. To address this question, we used a novel, brain penetrant, MLK3 inhibitor, URMC099. URMC099 efficiently inhibited the migration of breast cancer cells in an in vitro cell monolayer wounding assay, and an in vitro transwell migration assay, but had no effect on in vitro cell growth. We also tested the effect of URMC099 on tumor formation in a mouse xenograft model of breast cancer brain metastasis. This analysis showed that URMC099 had no effect on the either the frequency or size of breast cancer brain metastases. We conclude that pharmacologic inhibition of MLK3 by URMC099 can reduce the in vitro migratory capacity of breast cancer cells, but that it has no effect on either the frequency or size of breast cancer brain metastases, in a mouse xenograft model.